Pace variability of a female race walker in a 20 km racing events - Pupis, M.; Czakova, M.; Pavlovic, R. (Acta Kinesiologica, 2016)
The paper deals with the issue of pace variation in race walking during a 20 km racing event. The research has shown that the female race walker slows down considerably from the fifteenth kilometre of the racing event. The deceleration lasts approximately up to the eighteenth kilometre. The female race walker is able to accelerate again in the final two kilometres of the racing event. We have discovered that the female race walker achieves the best results in the qualifiers. All her personal records were achieved in the qualifiers. The female race walker improved only once in the first top-level event and achieved the worst results in the second top-level event. By means of the ANOVA statistical method, we were able to determine statistically significant pace variations between the individual racing events (p<0,01) and pace variations in the split times- kilometres (p<0,01). We noticed an interaction (p<0,01) between the pace in individual kilometres and the course of the racing events, or more precisely with the sports performance. The significant variations in the individual split times point to the high pace variability in the 20km distance. This variability corresponds with the current level of special endurance in the given racing event. Based on our discovery, we advise the race walker to focus more on pace endurance and special pace during the training process.